Is 13-Valent Pneumococcal Conjugate Vaccine (PCV13) Combined With 23-Valent Pneumococcal Polysaccharide Vaccine (PPSV23) Superior to PPSV23 Alone for Reducing Incidence or Severity of Pneumonia in Older Adults? A Clin-IQ - Hayward, Starla (J Patient Cent Res Rev, 2016)
Pneumonia infection is a significant cause of morbidity and mortality worldwide. In addition to the public health concerns, pneumonia also accounts for a significant cost to the health care system. Currently there are two leading vaccines targeted against S. pneumoniae: 23-valent pneumococcal polysaccharide vaccine (PPSV23) and 13-valent pneumococcal conjugate vaccine (PCV13). Until recently the recommendation for adult pneumonia vaccination has been a single dose of PPSV23 for all adults 65 years and older. However, concerns were raised regarding the vaccine’s efficacy due to the persistent burden of pneumococcal disease in the elderly population. This paper focuses on two trials which evaluate the safety and efficacy of PCV13 in the adult population. The first study reveals improved immune response with the addition of PCV13 to PPSV23, while the second shows PCV13 was effective in the prevention of vaccine-type community-acquired pneumonia. The two studies observed adequate safety profiles for PCV13 in series with PPSV23 and with PCV13 compared to placebo.